Clinical Value of Echo-Tracking in Gestational Diabetes Mellitus - Zhou, Youxia; Lan, Qianyu; Li, Yuan; Qi, Lin; Dong, Yiming; Zhou, Haixia; Zhang, Jiefang (Experimental and Clinical Endocrinology & Diabetes, 2022)
Background Vascular endothelial function plays an essential role in gestational diabetes mellitus (GDM) pathogenesis. Vascular elasticity is evaluated by the echo-tracking (ET) technique. In this study, we aimed to assess the clinical value of the ET technique in women with GDM and provide a basis for early evaluation and prevention of gestational diabetes.Methods Sixty-five patients with GDM and 65 gestational week-matched normal glucose tolerance pregnant women were enrolled in this study. The endothelial function parameters of pressure-strain elasticity coefficient (EP), the common carotid stiffness index (β), arterial compliance (AC), single-point pulsed-wave velocity (PWVβ), and augment index (AI) of bilateral common carotid arteries, were compared between the GDM and control groups by using ET technique. The correlations between plasma glucose levels and ET parameters were also analyzed.Results Our results indicated that EP, β, PWVβ, and AI were significantly higher in the GDM group (p<0.05), whereas AC was significantly lower in patients with GDM than in the control group (p<0.001). In addition, fasting plasma glucose and plasma glucose level after 2 h oral glucose tolerance test was correlated with ET parameters of EP, β, PWVβ, AI, and AC.Conclusions The application of ET technology to gestational diabetes women could provide a basis for early evaluation and prevention of gestational diabetes. It would detect early and accurate signs of diabetes in pregnant women and provide a timely and reasonable clinical treatment plan to reduce and delay the occurrence of complications.
Keywords: echo tracking technique; gestational diabetes mellitus; OGTT; vascular endothelial function; glucose